Living functional hydrogels generated by bioorthogonal cross-linking reactions of azide-modified cells with alkyne-modified polymers - Koji Nagahama (Nature Portfolio, 2018)
Cells are often passively encapsulated in hydrogels for a wide range of applications. Here, the authors report on a method of incorporating the cells into the hydrogel using bioorthogonal click reactions to link azide-modified cells with biocompatible polymers to create cell-based materials.